Service Design Guidelines for New Types of Wellness Tourism - Riccardo Bonazzi; Vincent Grèzes; Valérie Barbey (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
In this article, we describe the preliminary results of an ongoing project aiming at increasing the attractiveness of Alpine destinations in Switzerland, by means of a very widespread hotel. We investigate how to design new services for wellness tourism, which target (a) “young elderly”, whose age is comprised between 60 and 75 years, and (b) enterprises interested in meetings, incentives, conferencing and events. The first customer segment is known to be proactive in seeking to improve or maintain health and quality of life, while medical tourists generally travel reactively to receive treatment for a diagnosed disease or condition. The second customer segment mostly seeks for complementary activities to be done after work or as main topic for a seminar. Accordingly, we have conducted interviews with different stakeholders: hotel managers, owners of firms producing natural components for wellbeing and tourist officers. In the end, we highlight a set of relevant findings that should be taken into account when setting up wellness tourism in a dispersed area.
Keywords: Z3; 330; wellness tourism; young elderly; destination management